Basic Japanese E-learning Application with Prototype Methodology - Najaemin F. Sianturi (Institute of Computer Science (IOCS), 2021)
Basic Japanese E-learning application is computer software intended as a tool that provides convenience and practicality in learning basic Japanese such as recognizing hiragana, katakana and is equipped with grammar and general conversation. The creation of an E-learning system in the field of learning is one thing that is expected to improve the quality and understanding of the general public in learning Japanese. The software development uses system development modeling with the Prototype Methodology, the analysis and design stages use the Object Oriented Methodology from Coad and Yourdon with modeling using UML, while the implementation uses the PHP programming language with the MYSQL Database Management System (DBMS). The result achieved is a learning application that provides convenience and practicality in understanding Japanese. This learning application is supported by multimedia elements so as to provide a more attractive and interactive appearance so that students can carry out learning activities more fun.